JIT and Small Companies - Noor Sarbani, Wan Muhammad; Nur Syamimi, Zulkefli; Zarith Sufia, Azlan; Sorooshian, Shahryar (AGBA, 2015)
Just-in-time manufacturing means producing the necessary items in necessary quantities at the necessary time. It is a philosophy of continuous improvement in which non-value-adding activities (or wastes) are identified and removed. Putting this concept into practice means a reversal of the traditional thinking process. In conventional production processes, units are transported to the next production stage as soon as they are ready. In JIT, each stage is required to go back to the previous stage to pick up the exact number of units needed.